18F-FDG PET in Giant Cell Arteritis. (February 2020) - Ahmadi Bidakhvidi, Niloefar; Goffin, Karolien; Van Laere, Koen; Gheysens, Olivier; Blockmans, Daniel
Abstract : Abstract: An 87-year-old man, without significant history, presented at the emergency department with recurrent episodes of fever and weight loss for several weeks without diagnosis, despite extensive routine investigations including conventional imaging. 18 F-FDG PET/CT revealed strongly increased uptake in the peripheral vessels of the upper and lower limbs with relative sparing of the larger vessels. Temporal artery biopsy was positive for arteritis. The diagnosis of giant cell arteritis with mainly involvement of upper and lower limbs was made, and treatment with high-dose oral methylprednisolone was started, resulting in a rapid clinical and biochemical improvement.